E-LKPD Based on Problem-Based Learning on the Topic of Becoming Environmental Heroes for Fourth Grade Elementary School Students: - - Ni Kadek Sutarmiasih; Dewa Gede Firstia Wirabrata; Ni Wayan Eka Widiastini (Universitas Pendidikan Ganesha, 2026)
This study was motivated by the limited use of technology-based teaching materials in science and social studies (IPAS) learning for fourth-grade elementary school students. The results of observations showed that learning activities were still dominated by the use of black-and-white printed modules that were less interactive and had not been able to optimally accommodate students' enthusiasm and learning needs. This condition affected students’ conceptual understanding, which was not yet optimal. The needs analysis showed that all students and teachers supported the development of electronic teaching materials that are more innovative, contextual, and problem-solving based. This study employed a Research and Development approach with a descriptive quantitative method using the ADDIE model, which consists of the stages of analyze, design, development, implementation, and evaluation. The research subjects included material experts, media experts, a fourth-grade teacher, students in individual trials, and students in small group trials. The object of this study was a Problem Based Learning-based e-worksheet (e-LKPD) on the topic Becoming Environmental Heroes. The results showed that the developed e-LKPD obtained very good qualifications from material experts and media experts. The practicality test also showed that teacher and student responses were in the very good category. Therefore, the Problem Based Learning-based e-LKPD was declared valid, practical, and feasible for use in elementary school IPAS learning. The implications of this study indicate that the e-LKPD has the potential to increase student engagement, support contextual learning, and assist teachers in optimizing the use of learning technology in elementary schools.